2016
DOI: 10.1186/s11689-016-9174-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual memory profile in 22q11.2 microdeletion syndrome: are there differences in performance and neurobiological substrates between tasks linked to ventral and dorsal visual brain structures? A cross-sectional and longitudinal study

Abstract: BackgroundChildren affected by the 22q11.2 deletion syndrome (22q11.2DS) have a specific neuropsychological profile with strengths and weaknesses in several cognitive domains. Specifically, previous evidence has shown that patients with 22q11.2DS have more difficulties memorizing faces and visual-object characteristics of stimuli. In contrast, they have better performance in visuo-spatial memory tasks. The first focus of this study was to replicate these results in a larger sample of patients affected with 22q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…; Bostelmann et al . ), individuals with 22q11.2DS exhibited lower memory scores on the C‐BVRT compared with healthy controls. Furthermore, we found that individuals affected by the syndrome with shorter average fixation duration ratios (indicating shorter fixations on the peripheral figures compared with the principal figures) were characterised by poorer accuracy on the C‐BVRT.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…; Bostelmann et al . ), individuals with 22q11.2DS exhibited lower memory scores on the C‐BVRT compared with healthy controls. Furthermore, we found that individuals affected by the syndrome with shorter average fixation duration ratios (indicating shorter fixations on the peripheral figures compared with the principal figures) were characterised by poorer accuracy on the C‐BVRT.…”
Section: Discussionmentioning
confidence: 83%
“…; Bostelmann et al . ) and clinical observations made by practitioners and educators who work with affected individuals. The present results additionally may help to shed light on effective learning strategies and useful adaptive measures, such as creating visually simple school material and pointing out elements that are located on the perimeter of the page and more easily missed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations